PEMBUATAN BOARD GAME UNITE AND FIGHT - Agung Wijoyo; Andre Andre; Richard Pramono (CALYPTRA, 2018)
cooperation is an important aspect that need to be taught as soon as possible, especially to teenager which is an important phase of individuality shaping. One of the example of such activity is outbound, but outbound is difficulties to be prepared, thus a convenient media to introduce the importance of cooperation is made in the form of board game with unique point in how to win the game. After that, board game with similar mechanic and companion app analyzed. The result then used to design the board game and companion app. The design of board game and companion app then made using adobe photoshop CS6 and unity. The board game made with cooperative play, action point allowance, variable phase order, programmed movement, dice rolling and grid movement mechanic. After made then the board game tested by doing blind test play with 10 people, after that each participant will be asked to fill the validation questionnaires, from their answers in the questionnaire inferred that the board game has positive result, which is to tell the participant that cooperation, communication and coordination is important, also the board game could attract their attention.